2020
DOI: 10.1002/adhm.202000655
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Intraperitoneal Aerosol Delivery of Nanoparticles: Proof of Concept and Preclinical Validation

Abstract: There is an increasing interest in intraperitoneal delivery of chemotherapy as an aerosol in patients with peritoneal metastasis. The currently used technology is hampered by inhomogenous drug delivery throughout the peritoneal cavity because of gravity, drag, and inertial impaction. Addition of an electrical force to aerosol particles, exerted by an electrostatic field, can improve spatial aerosol homogeneity and enhance tissue penetration. A computational fluid dynamics model shows that electrostatic precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 30 publications
2
20
0
Order By: Relevance
“…With regard to NPs delivered via IP injection, both tumor nodules harvested from random locations in the peritoneal space (namely region e and f), showed identical results regarding tumor accumulation and fluorescence signal intensity of pARG-HA NPs (with average fluorescence intensities between 100 and 150 a.u). Our findings are consistent with previous studies indicating that the intra-abdominal drug distribution after PIPAC is not as homogeneous as expected but varies between different regions of the peritoneal cavity 58 . As validated by granulometric analysis, about 97.5 vol.…”
Section: Pipac May Improve the In Vivo Accumulation And Penetration Of Parg-ha Nps Into Peritoneal Tumor Nodulessupporting
confidence: 93%
“…With regard to NPs delivered via IP injection, both tumor nodules harvested from random locations in the peritoneal space (namely region e and f), showed identical results regarding tumor accumulation and fluorescence signal intensity of pARG-HA NPs (with average fluorescence intensities between 100 and 150 a.u). Our findings are consistent with previous studies indicating that the intra-abdominal drug distribution after PIPAC is not as homogeneous as expected but varies between different regions of the peritoneal cavity 58 . As validated by granulometric analysis, about 97.5 vol.…”
Section: Pipac May Improve the In Vivo Accumulation And Penetration Of Parg-ha Nps Into Peritoneal Tumor Nodulessupporting
confidence: 93%
“…The main finding of our study is that both a positive charge and the electrostatic precipitation increase the depth of tissue penetration of CUR-PLGA-NPs. Our results are in line with prior data [13,27].…”
Section: Discussionsupporting
confidence: 92%
“…The proof-of-principle of combining PIPAC, electrostatic precipitation and nanoparticle formulation for enhancing tissue delivery was recently delivered. Simulations in silico showed that ePIPAC improved the spatial distribution of nanoparticles [13]. In a rodent model, ePIPAC significantly increased tissue penetration and provided a more homogeneous delivery of Nab-paclitaxel into the peritoneal tissue.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations